Solid-liquid two-phase flow and wear analysis in a large-scale centrifugal slurry pump. (August 2020) - Peng, Guangjie; Huang, Xin; Zhou, Ling; Zhou, Guoxin; Zhou, Hong
Highlights: One of the largest centrifugal slurry pumps used in the Chinese mining industry was investigated. Eulerian-Eulerian method was used to analyze the slurry flow for various particle concentrations. The numerical results were compared and validated by the results of field test. Abstract: Centrifugal slurry pumps are widely used in the mining and dredging industries. However, the flow passage components in the pump can become severely worn due to their low speeds, high flow rates, and high slurry concentrations. In the mining industry, slurry pumps often only last 20–30 days. The resulting frequent pump disassembly and installation not only consumes much time, but the frequent replacement of the flow passage components is very expensive. This study analyzed a heavy-duty slurry pump in the grinding circuit of an ore dressing plant. The Eulerian-Eulerian method was used to analyze the slurry flow for various particle concentrations and small volumetric flow rates. The analysis shows that for small flow rates, the pump flow is very unstable with significant backflow and intense local abrasion and as the particle concentration increases, the flow resistance increases, the backflow increases, and the local wall abrasion is aggravated. A grinding circuit slurry pump was field tested with the results showing that the location of the most severe local abrasion confirmed the simulation results.